Challenges of online medical education in Pakistan during Covid-19 pandemic - Manan, Sadia; Daterdiwala, Nida Fatima (Journal of the Pakistan Medical Association, 2022)
Dear Madam/Sir, The COVID-19 outbreak has swiftly changed into a worldwide pandemic. This transition has had adverse consequences for public institutions raising questions particularly for medical schools. (1) Following the pandemic, nationwide lockdown has impacted 89% of the world’s student population. (2) In this Letter, our focus is to highlight the challenges faced by medical students during this prolonged period of online education concluded by some suggestions to overcome them. A number of changes were done to address the imminent challenge of closure and improve the durability of educational systems in Pakistan. The primary shift was to plan and deliver learning sessions where students and teachers are geographically remote from each other. Online synchronous instruction sessions were quickly introduced using platforms like Zoom and Microsoft Team. (3) Although these efforts contributed to the efficient delivery of content, they also caused instructors, and learners to struggle with the process. (4) In an underdeveloped country like Pakistan, online learning is ineffective as majority of the students lack internet facilities due to technical and financial issues. Some of the other difficulties faced by students include absence of in person interaction with the tutor, lack of immediate tutor response and absence of on campus social interaction. (5) This effect of COVID-19 became an immediate concern among medical students. They were suspended from attending their clinical training which led to reduced exposure causing a pernicious effect on exam performance. A vast number of students missed the opportunity of doing electives abroad as most of them were cancelled due to the increasing number of cases. (6) To conclude, e-learning did influence the quality of medical education and therefore requires a collaborative approach to address the situation. There are some points we would like to suggest. Firstly, the teaching faculty should be given proper virtual training by allotting an IT professional to each one of them. Secondly, the lectures conducted should be interactive rather than being recorded in order to increase student engagement. This should be followed by routine assessments to evaluate their knowledge retention. Lastly, online problem-based learning techniques should be implemented so that the deficit of clinical exposure can be fulfilled. Despite the challenges posed by the pandemic, we must take this as an opportunity to develop e-learning programs which can open new horizons in distant-learning medical education.